Observations on the Phenology of Woody Species of Sariska Tiger Reserve in North-eastern Rajasthan - Yadav, Atar S.; Gupta, S. K. (Indian Forester, 2009)
Phenology of 39 species of shrubs and trees was studied in the Sariska Tiger Reserve Forest in North-East Rajasthan. The leaf fall, leaf flushing, flowering and fruit development was studied from December 2001 to November 2002. There were 24 deciduous woody species which represented more than 90 per cent of the vegetation in the study site. Leaf fall began from September onwards with the retreat of monsoon, attaining a peak value in February when about 35 per cent species were leafless. Leaf initiation began in hot and dry summer season from April untill the end of June when all the species had produced new leaves. Flowering and fruit development occurred throughout the year with one peak in hot and dry summer (March to April) and the another in rainy season (July to August). Thirty three per cent species flowered in the summer season followed by 26 per cent in the rainy season. Only three woody species produced flowers in the cold and dry winter season (December to January).